Expressão gênica dos alelos da proteína P21 na infectividade de cepas pertencentes a diferentes linhagens filogenéticas de Trypanossoma cruzi - Fernandes, Priscila Castro Cordeiro (2013)
Chagas disease was first described a century ago, is still endemic in 21 countries and it is known that the causative parasite, Trypanosoma cruzi is characterized morphologically by presenting three distinct evolutionary stages: epimastigote , trypomastigote and amastigote. Its life cycle is heteroxenic and infection by T. cruzi has a variable clinical presentation with acute and chronic. This parasite has a pattern of evolution reticulated, with a predominance of clonal propagation and occasional events of genetic recombinationation, which originate hybrid strains. Thus, we performed several studies based on the electrophoretic profile that determined groups of strains of this parasite with similar characteristics, called zymodemes, well , it was the determination of six zymodemes or DTUs (T. cruzi I- VI ), in our case, use strains G (TcI) , Y (TcII), RN-19 (TcIII) and CL (TcVI). With respect to cell invasion, it is known that the polymerization of the actin cytoskeleton is essential for remaining parasites as well as the internalized fusion of lysosomes and among the arsenal of molecules involved in cell invasion by different infectious forms of T. cruzi, we have the P21, a secreted protein that has a dependent activity of PI3-kinase. The P21 has two alleles of different sizes, and the minor allele, \"Esmeraldo-like\" (TcII ) and the higher allele, \"non-Esmeraldo-like\" (TcIII) . Our study aimed to analyze the expression of alleles of P21 in different strains and different forms of DTUs. Thus, we used primers for the two alleles and performed real time PCR . We obtained that despite alleles represent TcII and TcIII, were highly expressed in all forms of strains G (TcI) and Y (TCII) and P21 expression was higher in strains taken as \"little virulent\" (RN-19 and G) , demonstrating that its expression is not related to increased virulence.